Pengaruh Sistem Pengukuran Kinerja Dan Kejelasan Peran Terhadap Kinerja Karyawan - Siti Khoirina (Universitas Bandar Lampung (UBL), 2013)
This study aims to examine the effect of performance measurement systems and role clarity on the performance of employees, especially employees of banking in Lampung, Palembang, Jambi and Bengkulu. This study is expected to benefit over the role of performance measurement and clarity.Based on the results of the test by using partial least squares (PLS) SPK known that directly influence the performance of employees and indirectly through role clarity. In addition to seeing how the indirect effect of role clarity on the relationship between the SPK and the performance of employees, the authors conducted a track test. Based on the test track using Sobel's test found that SPK relations and employee performance is influenced by factors mediating role clarity.